An Analysis of the Journey of Open and Distance Education: Major Concepts and Cutoff Points in Research Trends - Çakıroğlu, Ünal; Kokoç, Mehmet; Gökoğlu, Seyfullah; Öztürk, Mücahit; Erdoğdu, Fatih (Athabasca University Press, 2019)
In an effort to understand trends in open and distance education more comprehensively, this study aims to identify the research trends, major concepts, and cutoff points in the articles published between 2009 and 2016. From five major peer-reviewed journals, a total of 989 articles were analyzed through a systematic literature review process using content analysis. The articles were coded based on the following three categories: level, topics, and sub-topics. The results indicated the followings: (1) emerged main themes in the articles were foundations of open and distance education, instructional process, and effects of applications; (2) there was an upward growth in the publishing of the articles on massive open online courses, open educational resources, and students’ perspectives; (3) new pedagogical approaches and online learning design played a triggering role in the research topics; and (4) technological and pedagogical developments between 2011 and 2012 had an influence on the tendency of the articles. In addition, we explored cutoff points so that they may provide insights and valuable hints for researchers to design new studies in open and distance education field. Discussions about the gaps in the state-of-the-art trends and directions about future research were also included.
Keywords: Content Analysis; content analysis; Review Study; research trends; open and distance education; review study; Open and Distance Education; Research Trends; 4. Education